HfO2‐Based Ferroelectrics Applications in Nanoelectronics. Issue 5 (11th February 2021) - Dragoman, Mircea; Aldrigo, Martino; Dragoman, Daniela; Iordanescu, Sergiu; Dinescu, Adrian; Modreanu, Mircea
Abstract : This article is dedicated to HfO2 ‐based ferroelectrics applications in nanoelectronics, especially to topics not well developed up to now, such as microwaves, energy harvesting, and neuromorphic devices working as artificial neurons and synapses. Other well‐covered topics in the literature, such as memories or negative‐capacitance ferroelectric field‐effect transistors, will be only briefly mentioned. The main impact of HfO2 ‐based ferroelectrics is the possibility of using them for fabricating at the wafer‐level complementary metal oxide semiconductor (CMOS) compatible high‐frequency devices, such as phase‐shifters, antenna arrays, or filters with a high degree of tunability and miniaturization, as well as energy harvesting devices and neuromorphic key components. In addition, the recent transfer of 2D materials on HfO2 ferroelectrics has demonstrated new physical effects, such as opening a 0.2 eV bandgap in graphene monolayers, and allows the manufacture of very high‐mobility field‐effect transistors (FETs) based on graphene/HfZrO. Abstract : HfO2 ‐based ferroelectrics applications in nanoelectronics are discussed, especially in topics not well developed up to now, such as microwaves, energy harvesting, and neuromorphic devices working as artificial neurons and synapses.